Bioinformatic analysis of FOXN3 expression and prognostic value in pancreatic cancer - Yu, Wei; Diao, Yongkang; Zhang, Yi; Shi, Ying; Lv, Xiangkang; Zhang, Chengwu; Zhang, Kangjun; Yao, Weifeng; Huang, Dongsheng; Zhang, Jungang (Frontiers in Oncology, 2022)
Forkhead box N3 (FOXN3) inhibits tumor proliferation as a transcriptional inhibitor in most cancers, but the opposite effect is seen in pancreatic cancer. To confirm and investigate this phenomenon, FOXN3 expression was detected using GEPIA2 in a variety of carcinomas and was found to be highly expressed in pancreatic cancer. Kaplan-Meier plotter was then used for survival analysis, revealing that high FOXN3 expression in pancreatic cancer might be associated with a poor prognosis. Similarly, clinical samples collected for immunohistochemical staining and survival analysis showed consistent results. The RNA-seq data of pancreatic cancer patients from the TCGA were then downloaded, and the differential expression gene set was obtained using R for gene set enrichment analysis (GSEA). The intersection of the above gene sets and FOXN3-related genes was defined as related differentially expressed gene sets (DEGs), and enrichment analysis was performed using Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG). Finally, we analyzed the relationship between FOXN3 and immune infiltration in pancreatic cancer. Collectively, our findings reveal that FOXN3 is involved in the occurrence and progression of pancreatic cancer and may be useful as a prognostic tool in pancreatic cancer immunotherapy.